2023
DOI: 10.1101/2023.09.15.23295612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The epidemiology of periportal fibrosis and relevance of currentSchistosoma mansoniinfection: a population-based, cross-sectional study

Seun Anjorin,
Betty Nabatte,
Simon Mpooya
et al.

Abstract: Background: Intestinal schistosome infections are known to cause periportal fibrosis (PPF). Yet, the epidemiology of PPF remains poorly understood, especially in settings endemic with Schistosoma mansoni. Methods: We randomly sampled 1442 households from 38 villages in Mayuge, Buliisa, and Pakwach Districts of Uganda within the SchistoTrack Cohort to examine 2834 individuals aged 5-90 years. PPF was diagnosed using ultrasound and image patterns C-F from the Niamey Protocol. S. mansoni infection status/intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…There have been calls for integrated control in these settings, including the use of exposure reduction interventions [36]. Our study was conducted in three districts that each had received over 13 rounds of MDA since the year 2003 [37]. Yet, we found that hotspot villages were associated with lower rates of water contact when compared to villages with <50% infection prevalence.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There have been calls for integrated control in these settings, including the use of exposure reduction interventions [36]. Our study was conducted in three districts that each had received over 13 rounds of MDA since the year 2003 [37]. Yet, we found that hotspot villages were associated with lower rates of water contact when compared to villages with <50% infection prevalence.…”
Section: Discussionmentioning
confidence: 91%
“…Kato-Katz stool microscopy and point-of-care cathodic antigen (POC-CCA) diagnoses were completed for schistosomiasis as described in Anjorin et al [37]. Readings were converted to eggs per gram (EPG) of stool.…”
Section: S Mansoni Infectionmentioning
confidence: 99%
“…The protocol also requires further instructions on how to standardise probe sweeps of the abdomen. Studies are currently underway in the SchistoTrack Cohort [ 54 ], a prospective cohort study on chronic schistosome infection and schistosomal PPF in Uganda, to create more specific and standardised guidance on how to apply the Niamey protocol.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to make a full assessment of the use cases of ultrasound in schistosomal PPF grading in the context of monitoring, evaluation, surveillance and elimination of hepatic schistosomiasis as a public health issue. An inspiration for this research could be the ‘Target Product Profile’ published by the WHO for schistosome infection diagnostics [ 53 , 68 ], along with WHO guidance on diagnostic ultrasound [ 54 , 69 ]. Future studies could investigate developing a target product profile for ultrasound staging of schistosomal PPF, establishing a reference standard to improve control of hepatic schistosomiasis-associated morbidity.…”
Section: Discussionmentioning
confidence: 99%